A revision of the ovuliferous fructifications of glossopterids form the Permian of South Africa - Adendorff, Rosemary (My University, 2009)
A comprehensive re-assessment of the South African ovuliferous glossopterid fructifications was conducted. This involved the creation of a database of quantitative and descriptive information based on over 500 specimens from 14 localities in the northern and eastern Karoo Basin and the Bushveld Basin. Specimens belonging to four families, thirteen genera and 24 species were measured in detail, re-described, re-evaluated and in many cases, existing diagnoses were emended. In total, this revision effected the creation of four new genera, one new species and emendations to two families, seven genera and thirteen species. All taxa were photographed, and representative specimens were drawn and reconstructed. An illustrated key to the ovuliferous glossopterid fructifications was compiled as a guide to the identification of all known species from South Africa. The South African literature on glossopterid polysperms was reviewed, with reference to discoveries from other parts of Gondwana. All the glossopterid ovuliferous fructifications examined were impression fossils, and a major component of the project was to re-evaluate the structure and morphology of the specimens from a taphonomic perspective. Although not widely taken into account in palaeobotanical studies, impression fossils are essentially moulds of the original plant, providing valuable three-dimensional information which is easily overlooked. This approach led to the discovery of several radical, new morphological types in well-known taxa. These discoveries could change the way glossopterid homologies are interpreted in the future. Additionally, these structures may help to resolve some of the conflicting reports regarding the presence of more than one set of cuticle per fructification, and sterile scales. Hirsutum intermittens was found to have a peculiar dual wing structure, and was transferred to a new genus, Bifariala. In addition to the primary wing with its tapered base, extended apex and apically inclined striations, an additional, secondary wing was recognised in these fructifications, which has a structure similar to that of Scutum and Gladiopomum. Hirsutum leslii was found to possess a unique, hood-like wing which arched over the seed-bearing surface iv of the fructification, partially enclosing the ovules, which were in many cases found still attached to the fructification. The species was deemed to be a junior synonym of Elatra. The semi-enclosed structure of Elatra raised questions regarding the pollination and seed dispersal mechanisms employed by members of this genus. A review of the literature on Arberia, and examination of South African specimens, led to emendation of the genus to include the presence of a scalelike extension distal to the single seed attachment point at ultimate branch termini. Appreciation of the bifacial nature of some Arberia species, which bear lateral branches across one surface of a laminate primary axis has important implications for the recognition of homologies and establishment of evolutionary trends among members of the glossopterids. Existing ideas regarding the homologies and phylogeny of the glossopterids were refined and developed further. The glossopterid polysperms are considered to have evolved from a basal member of the Arberiaceae, with planation, fusion and reduction of lateral branches having given rise to fructifications of the Rigbyaceae and Dictyopteridiaceae. Members of the Lidgettoniaceae are thought to have been derived from members of the Dictyopteridiaceae. The hypothesised derivation of the glossopterid fertile structures from modified shoots rather than leaves, supports an affiliation with the cordaitaleans rather than the pteridosperms. The biostratigraphic and biogeographical significance and application of the South African genera of glossopterid polysperms was briefly evaluated.
Keywords: glossopterids; Permian; South Africa